Social networking sites and religious extremism among young people -The problem of mutual influence- - Ouadah, Newel; Bouaziz, Boubaker (Journal of Social Sciences and Humanities, 2022)
This research paper discusses the issue of the mutual influence between social networking sites and the phenomenon of religious extremism among young people. We tried to describe the nature of the role that these networks could play in spreading religious extremism among youth users. In order to achieve the general objective of this study, we focused on the necessity of familiarity with the various conceptual and semantic contexts of the term religious extremism and its conceptual synonyms, in addition to identifying the concept and types of social networking sites, and highlighting its most important features and characteristics that qualified it to be the tool of extremists and their extremists in spreading this. On a number of functions and roles discussed throughout this paper, according to the literature on the field of media and communication.